Evaluasi Usability Sistem E-Voting Menggunakan System Usability Scale Pasca Perancangan Ulang Antarmuka - David Sam Limbong; Hermawan Setiawan; Satria Tegar Bimantara; Reza Ardiansyah Yudhanegara (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
Although cryptographic security is often the main concern in e-voting system development, practical implementation failures are frequently associated with poor user interfaces that increase cognitive load and voting errors. This study evaluates the effectiveness of User-Centered Design (UCD) interventions in improving usability and voter confidence in an e-voting system. A one-group pretest-posttest design was applied to 36 respondents representing novice voters. Usability was measured using the System Usability Scale (SUS) before and after the interface redesign. The intervention focused on visual hierarchy, navigation consistency, status visibility, and error prevention. The results show a statistically significant improvement, with the mean SUS score increasing from 69.10 in the marginal category to 95.76 in the excellent category. The paired sample t-test produced t(35) = -7.3441 with p < 0.0001, while Cohen's d reached 1.2130, indicating a large practical effect. The standard deviation also decreased from 21.98 to 3.09, demonstrating a more consistent user experience. These findings indicate that interface optimization is essential for strengthening accessibility, voting accuracy, and user trust in digital democracy systems.